Verbal fluency performance across different neurological disorders: a preliminary investigation - Paunović, Verica; Vuković, Mile (Specijalna edukacija i rehabilitacija, 2026)
Introduction. Language disorders can arise as a consequence of various neurological conditions, affecting communication and cognitive functioning. Aim. The aim of this study was to compare verbal fluency in individuals with different neurological disorders. Method. The sample consisted of 45 participants divided into three clinical groups according to the etiology: 15 post-stroke patients, 15 individuals with traumatic brain injury, and 15 patients with multiple sclerosis. The control group comprised 16 neurologically healthy participants. Phonemic and semantic verbal fluency tasks were administered. Results. Results indicated statistically significant differences in both phonemic and semantic fluency between each clinical group and the control group. Stroke patients demonstrated significantly lower performance on both phonemic and semantic fluency tasks compared to those with traumatic brain injury and multiple sclerosis. Conclusion. All three clinical groups with neurological disorders showed reduced verbal fluency abilities compared to healthy controls. These findings suggest that verbal fluency is frequently impaired across neurological disorders of different etiologies, regardless of clinical presentation.
Keywords: verbal fluency; stroke; traumatic brain injury; multiple sclerosis